Comparing inflation and price level targeting: the role of forward guidance and transparency - Seppo Honkapohja; Kaushik Mitra (Bank of Finland, 2015)
We examine global dynamics under learning in New Keynesian models with price level targeting that is subject to the zero lower bound. The role of forward guidance is analyzed under transparency about the policy rule. Properties of transparent and non-transparent regimes are compared to each other and to the corresponding cases of inflation targeting. Robustness properties for different regimes are examined in terms of the domain of attraction of the targeted steady state and volatility of inflation, output and interest rate. We analyze the effect of higher inflation targets and large expectational shocks for the performance of these policy regimes.
URN:NBN:fi:bof-201504091146
Keywords: E63; E52; E58; 330